The tattered cover - Adams, Ellery (Adams, Ellery. Secret, Book, and Scone Society novel., 2025)
"As the residents of Miracle Springs, North Carolina, select their costumes, plan parties, and get excited for a night of tricks or treats, Nora joins in on the festivities by hosting medium memoirist Lara Luz at the bookstore. Charismatic and compelling, Lara mesmerizes the audience with her life story. Struck by a bolt of lightning as a child, she was pronounced dead only to be resurrected with the ability to connect with those on the other side. Lara performs a reading for a select group of bookstore patrons when the encroaching storm knocks out the power. In the sudden darkness, howling cold winds intensify, and Lara clutches her heart, collapsing dead without warning. But Nora doesn't believe she died of natural causes. Not one member of the psychic's reading group--which includes the town's widower pharmacist, an urgent care nurse, a mystery author, and even truculent Deputy Hollowell--were admirers of Lara. Nora confirms this when she stumbles upon Lara's journal in the aftermath of her death. For within its leathery bound pages are the medium and her clients' deepest and darkest secrets, written in code ora and the Secret, Book, and Scone Society must sift through the suspects and their motives to uncover which one of them is a killer before he or she is tempted to strike again..."--